SUPERVISI AKADEMIK PENGAWAS UNTUK MENINGKATKAN KOMPETENSI KEPALA MTS N 1 BANDUNG - Hanafiah; Ratnawulan, Teti; Dahlan, Elon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the effectiveness of academic supervision conducted by supervisors in improving the competence of the principal of MTs Negeri 1 Bandung. The research focuses on four main aspects: supervision planning, supervision implementation, supervision evaluation, and follow-up supervision. Data were collected through interviews, observations, and documentation. The results show that although academic supervision is carried out with the goal of enhancing the principal’s competence, shortcomings remain in the planning and implementation, which tend to focus more on administrative aspects rather than on developing the principal’s academic leadership competence. Similarly, the evaluation and follow-up of supervision are more concerned with document completeness than with improving the quality of academic leadership. This study recommends adopting a more needs-based, collaborative, and reflective approach to supervision to increase its effectiveness and support the professional development of the principal. Keywords: Academic Supervision, Principal Competence, Academic